PENGARUH MODEL PEMBELAJARAN COOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA POWERPOINT INTERAKTIF TERHADAP HASIL BELAJAR IPS PESERTA DIDIK KELAS IV SDN 20 INDARUNG - Jawharatul Husniah; Ade Irma Suryani; Siti Aisyah; Intania Ananda Jonisa; Ardi Saputra Aceh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the low social studies learning outcomes of fourth-grade students at SDN 20 Indarung, as indicated by the number of students who had not achieved the Minimum Learning Achievement Criteria. The learning process was still dominated by lecture, question-and-answer, and simple discussion methods, causing students to be less active and less motivated in learning. This study aimed to determine the effect of the Cooperative Learning model of the Teams Games Tournament (TGT) type assisted by interactive PowerPoint media on students’ social studies learning outcomes. This research employed a quantitative approach with a quasi-experimental method using a Posttest Only Control Group Design. The population consisted of all fourth-grade students of SDN 20 Indarung, comprising two classes. The sampling technique used was total sampling, with class IV A as the experimental class and class IV B as the control class. The research instrument was a multiple-choice objective test. Data were analyzed using normality tests, homogeneity tests, and the Mann–Whitney U test. The results showed a significance value of 0.003 < 0.05; therefore, H₀ was rejected and H₁ was accepted. This indicates that there was a significant effect of implementing the Cooperative Learning model of the Teams Games Tournament (TGT) type assisted by interactive PowerPoint media on the social studies learning outcomes of fourth-grade students at SDN 20 Indarung. This was evidenced by the higher average posttest score of the experimental class compared to the control class. The implementation of the TGT learning model assisted by interactive PowerPoint media was able to improve students’ activeness, cooperation, motivation, and understanding in social studies learning.